Sustainable Rice Value Chain and Local Economic Policy: Building Competitiveness in Sidodadi Village - Faried, Annisa Ilmi; Arnita, Vina; Ulzannah, Nisa (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study examines the sustainable rice value chain in Sidodadi Village and evaluates how local economic policies can enhance regional competitiveness within Indonesia's agricultural sector. Rice production remains central to rural livelihoods, yet smallholder farmers face persistent challenges, including limited market access, inadequate post-harvest infrastructure, and fragmented policy frameworks. Through a mixed-methods case study approach combining qualitative interviews with 45 stakeholders and quantitative value chain analysis across 120 farm households, this research identifies critical bottlenecks in production, processing, and distribution stages. Findings reveal that coordinated local policies integrating sustainable agricultural practices, cooperative strengthening, and digital market linkages can increase farmer income by 23-31% while reducing environmental degradation. The study contributes two original frameworks: a multi-stakeholder governance model for rice value chains and a localized policy toolkit adaptable to smallholder contexts. Policy implications emphasize decentralized decision-making, investment in agro-processing facilities, and capacity building for farmer organizations. These interventions collectively build competitive advantage while ensuring environmental sustainability and social equity in rural economies.